Optimization of Bifidobacterium pseudocatenulatum KAKii cultivation conditions for exopolysaccharide production by using response surface methodology - Mahdi, Aliza; Musa, Maslinda; Ahmad, Siti Aqlima; Abdul Khalil, Khalilah (Malaysian Society for Microbiology, 2019)
Aims: Bifidobacteria is a non-motile, Gram-positive, strictly anaerobic and non-spore-forming bacteria that can produce exopolysaccharide (EPS). EPS is a polymer of sugars, long chained polysaccharide which have been shown to give benefit towards human health. The optimum conditions for EPS production by Bifidobacterium are still scarce. Therefore, a study was conducted to optimize the growth conditions (pH, temperature and cultivation time) for a better improvement of EPS production. Methodology and results: Three Bifidobacterium strains were cultured and the highest EPS producing strain was selected for optimization. Response Surface Methodology (RSM) was used to optimize the growth conditions for a maximum EPS production. Subsequently, EPS was characterized by using FT-IR and GC-MS. Based on the result obtained, B. pseudocatenulatum KAKii had the highest EPS production compared to the other two strains namely B. pseudocatenulatum ATCC 27919 and B. animalis. Meanwhile, the optimization of the three factors towards selected strain found that EPS produced crucially depends on time of cultivation (23.59 h) other than pH (5.0) and temperature (34.75 °C). The validation showed that the predicted and experimental values were not significantly different (P > 0.05), indicating that the developed model is fitted well for the optimization. Meanwhile, FT-IR and GC-MS results showed that the EPS was composed of D-glucose, mannose, galactose, maltose and acetic acid as by-product. Conclusion, significance and impact of study: This result showed that the EPS produced by B. pseudocatenulatum KAKii is from hetero-exopolysaccharide group with acetic acid as by-product made them a possible anticancer agent in future.